Education 3640. Problems and issues in special education. No. 03. Integration - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
Dr. Karagianis introduces a video originally produced for the "Issues in Education program," wherein Dr. Nesbitt discusses the issue of integration with Cathy Boak. "With Dr. W. Nesbit, Cathy Boak"; "An ETV Colour Production."